2019
DOI: 10.26858/jptp.v5i1.8199
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENAMBAHAN BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP MUTU PERMEN KARAMEL SUSU

Abstract: This study aims to determine the effect of adding red dragon fruit to the chemical and hedonic content of caramel milk. This study used a method of adding 20%, 30%, and 40% red dragon fruit pulp for caramel milk candy with a cooking time of 2 hours at 80˚C. This research is a quantitative study (experiment) using a completely randomized design (CRD) with 4 treatments, each control, 20%, 30%, and 40% with 3 replications. The research data was obtained from the results of chemical testing (moisture content, ash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…One fruit that is high in nutrients and has an attractive color is the red dragon fruit (Hylocereus polyrhizus). This fruit is has a sweet sour taste with an attractive purplish red color [10,11]. In addition, red dragon fruit is a tropical fruit that has not been used optimally and is generally only consumed directly.…”
Section: Introductionmentioning
confidence: 99%
“…One fruit that is high in nutrients and has an attractive color is the red dragon fruit (Hylocereus polyrhizus). This fruit is has a sweet sour taste with an attractive purplish red color [10,11]. In addition, red dragon fruit is a tropical fruit that has not been used optimally and is generally only consumed directly.…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of a product is determined by the moisture content of the raw and supporting materials used. According to Marlina et al [21], in 100 g of red Dragon fruit contains 80-90 g water. 2.97 ± 0.17 c Fat 1.14 ± 0.39 b 1.07 ± 0.24 b 1.20 ± 0.37 b 0.65 ± 0.05 a 0.63 ± 0.14 a Notes: T0 (control, no Dragon fruit), T1 (30% Dragon fruit), T2 (35% Dragon fruit), T3 (40% Dragon fruit), T4 (45% Dragon fruit).…”
Section: Resultsmentioning
confidence: 99%
“…Marlina et al [21] reported that milk caramel candy with the addition of 40% red Dragon fruit pulp produces the highest water content. The higher the concentration of red Dragon fruit pulp added, the more the effect on the water content of the milk caramel candy.…”
Section: Resultsmentioning
confidence: 99%
“…Buah naga mengandung antosianin dan pigmen betalain. Pigmen betalain merupakan pigmen yang memberi warna merah-violet (Marlina et al, 2019). Dengan demikian, semakin banyak puree buah naga yang ditambahkan akan menyebabkan warna velva semakin merah dan semakin menarik perhatian panelis.…”
Section: Warnaunclassified